2014
DOI: 10.1186/2045-3701-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of anti-cancer bioactive peptide with Cisplatin decreases chemotherapy dosing and toxicity to improve the quality of life in xenograft nude mice bearing human gastric cancer

Abstract: Background: A great challenge of cancer chemotherapy is to eliminate cancer cells and concurrently maintain the quality of life (QOL) for cancer patients. Previously, we identified a novel anti-cancer bioactive peptide (ACBP), a peptide induced in goat spleen or liver following immunization with human gastric cancer protein extract. ACBP alone exhibited anti-tumor activity without measurable side effects. Thus, we hypothesize that ACBP and combined chemotherapy could improve the efficacy of treatment and lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 23 publications
(24 reference statements)
2
27
0
Order By: Relevance
“…Cisplatin was dissolved in sterile phosphate buffered saline (PBS) for IP injection at 2 mg per kg body. Cisplatin treatment was initiated 2 days after tumor cell injection and repeated every 2 weeks . SFN was dissolved in sterile water and delivered by oral gavage three times per week (M/W/F) at 20 µmoles/dose beginning 2 days after tumor cell injection.…”
Section: Methodsmentioning
confidence: 99%
“…Cisplatin was dissolved in sterile phosphate buffered saline (PBS) for IP injection at 2 mg per kg body. Cisplatin treatment was initiated 2 days after tumor cell injection and repeated every 2 weeks . SFN was dissolved in sterile water and delivered by oral gavage three times per week (M/W/F) at 20 µmoles/dose beginning 2 days after tumor cell injection.…”
Section: Methodsmentioning
confidence: 99%
“…Bioactive peptides isolated from goat liver inhibited proliferation of human gastric cancer MGC‐803 cell line in a dose and time‐dependent fashion (Su and others ). Moreover, the primary purpose of a cancer clinical trial for a new cytotoxic drug is to identify the maximum tolerated dose, in view of the supposition that increment of efficacy and toxicity occurs monotonically as the dose increases.…”
Section: Cellular Targets For the Prevention And Treatment Of Cancermentioning
confidence: 99%
“…They are not only involved in innate immunity but also regulate adaptive immunity (1). Our previous study revealed that active peptides can perform biological functions by targeting certain miRNAs (2,3). Therefore, it has been suggested that inhibiting or restoring the function of a miRNA can provide a therapeutic benefit in certain diseases (4,5).…”
Section: Introductionmentioning
confidence: 99%